Effect of deoxynivalenol on apoptosis, barrier function, and expression levels of genes involved in nutrient transport, mitochondrial biogenesis and function in IPEC-J2 cells - Liao, Peng (Toxicol Res (Camb), 2017)
This study was conducted to determine the effect of 200 ng mL(–1) and 2000 ng mL(–1) deoxynivalenol (DON) on apoptosis, barrier function, nutrient transporter gene expression, and free amino acid variation as well as on mitochondrial biogenesis and function-related gene expression in the intestinal porcine epithelial cell line J2 (IPEC-J2) for 6 h, 12 h, and 24 h. Exposure to 200 ng mL(–1) DON inhibited the cell viability and promoted cell cycle progression from the G2/M phase to the S phase (P < 0.05). The data showed that the IPEC-J2 cell content of free amino acids, such as valine, methionine, leucine, and phenylalanine, was increased (P < 0.05) after treatment for 6 h; the aspartate, threonine, and lysine contents increased (P < 0.05) after treatment for 12 h; and the aspartate, serine, glycine, alanine, isoleucine, leucine, and lysine contents decreased (P < 0.05) after treatment for 24 h. The expression levels of barrier function genes, including zonula occludens 1 (ZO-1), occludin (OCLN), and claudin 1 (CLDN1), showed a significant reduction (P < 0.05). Moreover, the expression levels of differently regulated nutrient transporter genes, including B(0,+) amino acid transporter (B(0,+)AT) and sodium-glucose transporter 1 (SGLT1) genes, showed a significant decrease (P < 0.05), while the Na(+)-dependent neutral amino acid transporter 2 (ASCT2) and glucose transporter type 2 (GLUT2) showed a significant increase (P < 0.01). The expression levels of cytokine genes, including IL-8, and IL-1β genes, showed a significant increase (P < 0.05). Furthermore, the expression levels of mitochondrial biogenesis and function-related genes, including mitochondrial transcription factor A (TFAM) and nuclear respiratory factor-1 (NRF), mitochondrial single-strand DNA-binding protein (mt SSB) and mitochondrial polymerase r (mt polr), NADH dehydrogenase subunit 4 (ND4) and cytochrome c oxidase (CcOX) IV, CcOX V and cytochrome c (Cyt c), mammalian silencing information regulator-2α (SIRT-1), glucokinase and citrate synthase (CS), showed a significant increase (P < 0.05). Taken together, the present study indicated that 200 and 2000 ng mL(–1) DON could affect proliferation and cell cycle progression from the G2/M phase to the S phase and could mediate the expression levels of differently regulated barrier function, nutrient transport, and mitochondrial biogenesis and function-related genes.